2023
DOI: 10.3390/jcm12082799
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cognitive Impairment and Freezing of Gait in Patients with Parkinson’s Disease

Abstract: Background: Freezing of gait (FOG) is a common disabling symptom in Parkinson’s disease (PD). Cognitive impairment may contribute to FOG. Nevertheless, their correlations remain controversial. We aimed to investigate cognitive differences between PD patients with and without FOG (nFOG), explore correlations between FOG severity and cognitive performance and assess cognitive heterogeneity within the FOG patients. Methods: Seventy-four PD patients (41 FOG, 33 nFOG) and 32 healthy controls (HCs) were included. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…In PD patients, blood perfusion was significantly decreased in right anterior cingulate cortex compared with the normal controls [49]. Furthermore, amplitude of low-frequency fluctuation in right anterior cingulate cortex was positively correlated with freezing of gait [50], which was causally associated with cognitive impairment in PD patients [4, 33]. Taken together, these findings suggested that right anterior cingulate cortex might play an essential role in the development of cognitive impairment in PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PD patients, blood perfusion was significantly decreased in right anterior cingulate cortex compared with the normal controls [49]. Furthermore, amplitude of low-frequency fluctuation in right anterior cingulate cortex was positively correlated with freezing of gait [50], which was causally associated with cognitive impairment in PD patients [4, 33]. Taken together, these findings suggested that right anterior cingulate cortex might play an essential role in the development of cognitive impairment in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…It can occur at any disease stage, even at the prodromal phase and early stage of the disease [2, 3]. It is associated with faster disease progression and worse prognosis [1, 4], which draws plenty of attention to promote the early diagnosis and treatment of cognitive impairment during PD management. According to previous literature, PD patients can display the impairments of multiple cognitive domains, spanning episodic memory [5], verbal memory [6], executive function [7], visuospatial ability [8], and processing speed [9].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Cognitive impairment was also one of the most common non-motor features of PD patients 73 and associated with disease progression and outcome. [73][74][75] Cognitive impairment could occur at the early stage and even prodromal phase of PD. 73,[76][77][78] According to previous studies, PD patients could exhibit impairments of multiple cognitive domains, including verbal memory, [79][80][81] executive function, 82,83 visuospatial function, 84,85 episodic memory, [86][87][88] and processing speed.…”
Section: Discussionmentioning
confidence: 99%
“…Early hypotension, but not its symptom severity, increased dementia risk in PD patients by 14% while not being associated with other clinical or neuropathological variables [ 94 ]. PD patients with freezing of gait (FOG), an important risk factor for CI, exhibit worse global cognition, EF/attention, language memory and visuospatial functions [ 95 , 96 , 97 ]. Another risk factor for PDD is the overuse of anticholinergic drugs, especially in older PD patients with multimorbidities [ 98 ].…”
Section: Risk Factors Of CI In Pdmentioning
confidence: 99%